MRI-based Selection for Intra-arterial Stroke Therapy: Value of Pre-treatment DWI Lesion Volume in Selecting Acute Stroke Patients Who Will Benefit from Early Recanalization - Yoo, Albert J. (2009)
BACKGROUND AND PURPOSE: Recent studies demonstrate that an acute diffusion weighted imaging(DWI) lesion volume >70cm(3) predicts poor outcome in stroke patients. We sought to determine if this threshold could identify patients treated with intra-arterial therapy(IAT) who would do poorly despite reperfusion. In patients with initial infarcts <70cm(3), we sought to determine what effect recanalization and time to recanalization had on infarct growth and functional outcome. METHODS: We retrospectively studied 34 consecutive anterior circulation stroke patients who underwent pre-treatment DWI and perfusion weighted imaging(PWI) and subsequent IAT. Recanalization success and time to recanalization were recorded. Initial DWI and MTT lesion and final infarct volumes were determined. Patients were stratified based on initial infarct volume, recanalization status and time to recanalization. Statistical tests were performed to assess differences in clinical and imaging outcomes. Good clinical outcome was defined as a 3-month mRS≤2. RESULTS: Among patients with initial infarcts >70cm(3), all had poor outcomes despite a 50% recanalization rate, with mean infarct growth of 114cm(3). These patients also had the largest MTT volumes(p<0.04). Patients with initial infarct volumes <70cm(3) who recanalized early had the best clinical outcomes(p<0.008) with a 64% rate of mRS≤2 and the least infarct growth(p<0.03), with mean growth of 18cm(3). CONCLUSION: This study supports the use of an acute DWI lesion volume threshold as an imaging selection criterion for IAT. It also confirms the importance of early reperfusion in selected patients.